2009
DOI: 10.4161/oxim.2.4.8876
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in The Hippocampus During Experimental Seizures Can Be Ameliorated With The Antioxidant Ascorbic Acid

Abstract: Ascorbic acid has many nonenzymatic actions and is a powerful water-soluble antioxidant. It protects low density lipoproteins from oxidation and reduces harmful oxidants in the central nervous system. Pilocarpine-induced seizures have been suggested to be mediated by increases in oxidative stress. Current studies have suggested that antioxidant compounds may afford some level of neuroprotection against the neurotoxicity of seizures. The objective of the present study was to evaluate the neuroprotective effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 55 publications
1
52
0
2
Order By: Relevance
“…In the second experiment, 20 rats were randomly divided into four equal groups as noted above, and these animals were used for the evaluation of BBB permeability and levels of MMP-9. The dose of r-tPA and AA was selected based on the other investigations [14,18] and our preliminary results. The drugs were applied at 5 hr after the stroke onset.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second experiment, 20 rats were randomly divided into four equal groups as noted above, and these animals were used for the evaluation of BBB permeability and levels of MMP-9. The dose of r-tPA and AA was selected based on the other investigations [14,18] and our preliminary results. The drugs were applied at 5 hr after the stroke onset.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that antioxidant treatment with AA significantly reduces lipid peroxidation and increases superoxide dismutase and catalase activities after seizures induced by pilocarpine [14]. Moreover, AA is an essential antioxidant for scavenging free radicals in the brain and may protect endothelial function against the exacerbated ischaemic oxidative injury in diabetes [15].…”
mentioning
confidence: 99%
“…Besides its implication in many biological processes, vitamin C is a powerful reducing agent, participating in several antioxidant mechanisms (Santos et al, 2009) by directly scavenging radicals, mediating electron transfer to ascorbate-dependent peroxidases or regenerating membrane bound vitamin E that has been oxidized, e.g. by lipid peroxyl radicals (LOO • ), and thus indirectly limiting lipid peroxidation in cell membranes.…”
Section: Vitamin C and Vitamin Ementioning
confidence: 99%
“…Several beneficial functions have been attributed to vitamin C, e.g. as regulative factors that may influence gene expression, apoptosis and other cellular functions, and playing a role as a cofactor for several enzymatic steps in the synthesis of monoamines, amino acids, peptide hormones, and carnitine (Santos et al, 2009). …”
Section: Vitamin C and Vitamin Ementioning
confidence: 99%
“…These biomolecules are having an antioxidant profile which would be a strong basis for showing neuroprotection within the brain [9]. These biomolecules are natural compounds which are found in many fruits and vegetables and having much stronger antioxidative and neuroprotective activities [10]. The neuroprotective properties of Naringenin Inhibited LPS induced NOS and COX2 expression and suppressed the production of NO in microglial cells.…”
Section: Introductionmentioning
confidence: 99%